1994
DOI: 10.2466/pms.1994.78.3c.1303
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument for Measuring Parental Beliefs about Reading Aloud to Young Children

Abstract: This study assessed the psychometric properties of an instrument designed to measure parents' beliefs about the goals and process of reading aloud to young children. 155 parents of children ages 2 to 5 years completed the Parent Reading Belief Inventory. The inventory's items formed a single factor with high scores reflecting beliefs consistent with current theories of language acquisition and emergent literacy. The inventory had acceptable internal consistency (coefficients alpha for the scales ranged from .5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 8 publications
10
104
2
2
Order By: Relevance
“…Higher scores reflect more positive parental reading beliefs (PRB) regarding shared book reading. Test-retest reliability was .79 in the earlier study [12]. Cronbach's reliability estimated on the current sample was adequate (α= .89).…”
Section: Instrumentssupporting
confidence: 41%
See 1 more Smart Citation
“…Higher scores reflect more positive parental reading beliefs (PRB) regarding shared book reading. Test-retest reliability was .79 in the earlier study [12]. Cronbach's reliability estimated on the current sample was adequate (α= .89).…”
Section: Instrumentssupporting
confidence: 41%
“…The Parent Reading Belief Inventory was developed by DeBaryshe and Binder [12]. Higher scores reflect more positive parental reading beliefs (PRB) regarding shared book reading.…”
Section: Instrumentsmentioning
confidence: 99%
“…From Study 2, recall that we categorized caregivers with respect to implementation into four profiles using latent class analysis: sporadic (15%), late dropouts (7%), completers (34%), and nonstarters (44%). A comprehensive caregiver questionnaire was completed by caregivers at the start of the investigation, providing information about socioeconomic status (maternal education), home reading habits, household chaos, and the Parent Reading Belief Inventory (PRBI; DeBaryshe & Binder, 1994). The PRBI examines caregivers' perceptions about the value and benefits of reading with their children.…”
Section: Applying the Tdf To Caregivers Of Children With LImentioning
confidence: 99%
“…Maternal education based on a categorical scale to represent highest grade completed (1 = < 7th grade, 2 = 7th-8th grade, 3 = some high school, 4 = high school diploma, 5 = some college, 6 = university degree, 7 = postgraduate training). Reading belief items are from the Parent Reading Belief Inventory (DeBaryshe & Binder, 1994) and scored on a 1-4 scale ("reverse" items are reverse-scored, 1 = higher value); household chaos from the Chaos, Hubbub, and Order Scale (higher scores = more chaos; Matheny et al, 1995); Caregiver reading difficulty represents percentage of caregivers who reported receiving extra help for reading in high school; Reading frequency represents caregiver reported reading to child during a week, range of 0 (never read) to 8 (7+ sessions).…”
Section: Applying the Tdf To Caregivers Of Children With LImentioning
confidence: 99%
“…The questionnaire was adapted from Debaryshe and Binder (1994). The final version consisted of 39 items divided into 6 concepts.…”
Section: Toolsmentioning
confidence: 99%